A Microwave- irradiated Novel Superabsorbent Polymer Hydrogel (Guar gum-g- PAA): Synthesis, characterization and property studies - Pramilarani Behera; Tikina Rani Sethy; Prafulla K Sahoo (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2018)
The main aim of the present study was to synthesize Guar gum grafted poly acrylic acid (Gg-g-PAA) superabsorbent polymer (SAP) hydrogel via free radical emulsifier-free emulsion graft polymerization technique using microwave irradiation. The so prepared superabsorbent polymer hydrogel was characterized by Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric Analysis (TGA), Scanning Electron Microscopy (SEM). The properties like swelling ability and biodegradability were also studied which has a profound influence in agriculture, biomedicine, pharmaceutics, etc. The SAP may potentially be used for the fast release of medicine in high pH environment. It also may have found its application and sustainability in the removal of heavy metal ions from the waste water through adsorption leading to water remediation.